2020
DOI: 10.1186/s12877-020-01621-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic diseases and falls among a sample of older people in Finland

Abstract: Background: Falls are a major problem for older people and recurrent fallers are especially prone to severe consequences due to falls. This study investigated the association between chronic conditions and falls. Methods: Responses from 872 older persons (age 65-98) to a health questionnaire were used in the analyses. Characteristics and disease prevalence between recurrent fallers, one-time fallers and non-fallers were compared. A hierarchical clustering method was applied to find combinations of chronic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 45 publications
3
41
0
5
Order By: Relevance
“…We found that more than half of women aged 50-70 years old had a history of chronic diseases, and the top three were hypertension, osteoarthropathy and coronary heart disease, which is lower than the rates reported in other studies in China [18,25], possibly to do with age, household type, BMI, average monthly household income, and self-reported physical health. Age was a widely risk factor for chronic diseases, people were more likely to suffer from chronic diseases as they got older [26], consistent with a study reported in Finland [27]. Women lived in urban showed a higher prevalence, on the one hand, they kept bad lifestyles and lacked exercises [28].…”
Section: Discussionsupporting
confidence: 81%
“…We found that more than half of women aged 50-70 years old had a history of chronic diseases, and the top three were hypertension, osteoarthropathy and coronary heart disease, which is lower than the rates reported in other studies in China [18,25], possibly to do with age, household type, BMI, average monthly household income, and self-reported physical health. Age was a widely risk factor for chronic diseases, people were more likely to suffer from chronic diseases as they got older [26], consistent with a study reported in Finland [27]. Women lived in urban showed a higher prevalence, on the one hand, they kept bad lifestyles and lacked exercises [28].…”
Section: Discussionsupporting
confidence: 81%
“…Older adults in urban areas with chronic illness have a 3 times higher risk to fall than who did not have chronic illness. Chronic illness has significant impact in deteriorating physical function that increases the risk of falls [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The vertebral column is the longitudinal axis of the body responsible for guaranteeing the upright position against the action of gravity and enables walking. In the case of patients with rheumatic diseases, their functions are altered due to the involvement of the joints and adjacent structures, which will inevitably cause chronic pain, progressive movement limitation and disability 1,27 .…”
Section: Discussionmentioning
confidence: 99%